Lipids, Lipophilic Components and Essential Oils from Plant Sources - Azimova, Shakhnoza S.; Glushenkova, Anna I.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
An extensive collection of data on lipids and essential oils that can be extracted from a wide range of plant sources. Over 3,000 plant species are covered, arranged by broad family groups. For each plant detailed information is provided on the lipids, lipophilic compounds and oils that can be extracted from various parts of the plant, e.g. stem, leaves, fruit, seeds etc. References to peer-reviewed journal sources are provided throughout This unique reference will be of value equally to natural product chemists, botanists and those seeking sources of active compounds in pharmaceuticals, cosmetics and other commercial products.
Apiaceae -- Araliaceae -- Asteraceae -- Aoraginacea -- Cruciferae (Brassicaceae) -- Cucurbitaceae -- Ericaceae -- Euphorbiaceae -- Lamiaceae -- Leguminosae -- Malvaceae -- Onagraceae -- Ranunculaceae -- Rhamnaceae -- Rosaceae -- Rutaceae -- Salicaceae -- Solanaceae -- Organism Index.
Keywords: Chemistry; Food science; Chemistry, Organic; Bioorganic chemistry; Pharmacy; Biochemistry; Lipids; Chemistry; Organic Chemistry; Plant Biochemistry; Pharmacy; Lipidology; Bioorganic Chemistry; Food Science